2011
DOI: 10.1002/ibd.21672
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony stimulating factor blockade promotes ccr9+ lymphocyte expansion in Nod2 deficient mice

Abstract: Background-Ileal involvement in Crohn's disease (CD) is associated with NOD2 mutations and Granulocyte-Macrophage Colony Stimulating Factor auto-antibodies (GM-CSF Ab), and GM-CSF blockade promotes ileitis in Nod2/Card15 deficient (C15KO) mice. RALDH2 expressing dendritic cells (DC) and IL-4 promote CCR9 imprinting and small bowel homing of T lymphocytes, in conjunction with CCL25 expression by ileal epithelial cells (IEC). We hypothesized that GM-CSF neutralization promotes ileal disease by modulating express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Analysis of the CCL25/GM-CSF ratio indicates that H. pylori positive and negative gastroduodenitis are unrelated clinical entities. Our data support the observation made by Samson et al suggesting a role for GM-CSF and CCL25 in the pathogenesis of inflammatory gastrointestinal disease (Samson et al, 2011). These authors demonstrated that CD patients with high serum level of GM-CSF neutralizing antibodies had increased number of iliac epithelial cells expressing CCL25.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of the CCL25/GM-CSF ratio indicates that H. pylori positive and negative gastroduodenitis are unrelated clinical entities. Our data support the observation made by Samson et al suggesting a role for GM-CSF and CCL25 in the pathogenesis of inflammatory gastrointestinal disease (Samson et al, 2011). These authors demonstrated that CD patients with high serum level of GM-CSF neutralizing antibodies had increased number of iliac epithelial cells expressing CCL25.…”
Section: Discussionsupporting
confidence: 93%
“…In Crohn's disease altered expression of GM-CSF and CCL25 has been suggested to play a role in the pathogenesis of inflammatory gastrointestinal disease (Samson et al, 2011). Therefore, we sought to determine whether these two cytokines were involved in the pathogenesis of H. pylori -related gastroduodenitis.…”
Section: Resultsmentioning
confidence: 99%
“…7 Our studies in animal models have shown that GM-CSF promotes intestinal barrier function and effective responses to mucosal injury, suggesting a direct role for genetic or acquired variation in GM-CSF bioactivity in more aggressive CD disease behavior. 4,8 However, a role for neutrophil-intrinsic variation in GM-CSF signaling in cell function and disease complications in pediatric CD has not previously been explored.…”
Section: Introductionmentioning
confidence: 99%
“…We discovered that GM-CSF Ab are present in a subset of CD patients, and that titers increase with increasing age of onset, from VEO to EO pediatric disease, and further with adult-onset disease 21 . Overall, approximately fifty percent of CD patients exhibit high levels of GM-CSF Ab which are associated with reduced neutrophil phagocytic capacity, increased intestinal permeability and reactivity to the enteric flora, and expansion of effector T cells expressing the gut homing receptor CCR9 21-23 . This is of potential therapeutic interest, as an oral small molecule inhibitor of CCR9 is entering phase 3 clinical trials for CD, and we have found that CD patients with elevated GM-CSF Ab who are treated with current therapies progress more rapidly to stricturing behavior requiring surgery 24 .…”
Section: A More Common Cause For Reduced Innate Function In Pediatricmentioning
confidence: 99%